Bioinspired synthesis of pentalene-based chromophores from an oligoketone chain. Issue 50 (24th April 2018) - Saito, Yuki; Higuchi, Masayuki; Yoshioka, Shota; Senboku, Hisanori; Inokuma, Yasuhide
Abstract : Inspired by natural polyketide synthesis, pentalene-based, cross-conjugated chromophores were synthesized from an aliphatic oligoketone chain. Abstract : We report a bioinspired synthesis of 2, 5-dihydropentalene-based chromophores from an aliphatic oligoketone bearing 1, 3- and 1, 4-diketone subunits. Unlike the natural polyketone sequence, fused five-membered rings were formed via an intramolecular aldol condensation. A subsequent Knoevenagel condensation reaction with malononitrile furnished a multiply cross-conjugated π-system with low-lying LUMO levels. Furthermore, pentalenes obtained from a non-conjugated aliphatic chain exhibited visible absorption and solid-state fluorescence.